Documentation of aquatic birds with relation to feeding habits in a lentic freshwater tank of Karnataka, India - K Harish Kumar; B.R.Kiran (International Journal of Pharma and Bio Sciences, 2020)
Birds are the bio-indicator of aquatic ecosystem. They have played an unique role in the development and restoration of natural environment. Birds belong to the top level of food chain and their natural habitats have undergone change as a result of human activities. To conserve the birds in their natural places , there is a need to understand their feeding habits. The present study deals with the documentation of aquatic birds in Malenahalli tank of Bhadravathi taluk, Karnataka, India. During the investigation, 11 species of waterfowls belonging to 7 families were recorded in and around the water body. Out of 11 species, 5 species were categorized as piscivorous, 4 species carnivorous, and 1 species each of granivorous and omnivorous respectively. Out of 11species, 10 species were recorded as common and one is considered as very common species. The intimate linkages between aquatic bird species and their habitats make them useful for identifying ecosystem health. As such, they will be indicators of deteriorating habitat quality and environmental pollution, also as metrics to work out the success of restoration efforts. Combined with their ability to signal the eminent outbreak of diseases, birds are incredibly useful as indicators to both the fields of ecology and to human health.